YOUTH EMPOWERMENT THROUGH THE SINNGKONG CHIPS BUSINESS PROGRAMME BY KARANG TARUNA AS AN EFFORT TO CREATE EMPLOYMENT IN PANTAI CEMPA VILLAGE - Yakin, Husnul; Muyassaroh, Anis (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
The youth empowerment programme started with the fact that many youths in Pantai Cempa Village are out of school and unemployed. This has an impact on the economy of the community and youth in particular who act as the backbone of the family. This youth empowerment programme aims to create jobs and develop the human resources of the youth to create independence and prosperity through a cassava chips business programme by youth organisations in Pantai Cempa Village. The method used by the pengabdi in carrying out this activity is with 3 stages, namely the activity socialisation stage, the implementation stage and the preparation of activity reports. The social approach is in the form of obtaining permits for the implementation of activities from the village government and gathering 24 active youth from the youth organisation with the aim of socialising entrepreneurial activities. The results of this empowerment activity have had a good impact on improving the economy of village youth as evidenced by the increase in product requests to be marketed directly and through social media. A PT company in Medan city orders at least 12 boxes of cassava chips every month. Through this empowerment programme, the youth of Pantai Cempa Village have managed to earn a salary of 50,000 per day. This also adds to the high enthusiasm of the youth as seen from their participation and consistency in implementing cassava chip making as a programme of the Karang Taruna Desa Pantai Cempa. In this case, the village government has responded positively to the emergence of empowerment activities to achieve a more advanced economy.